(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
– Structural reliability of buildings has become an important issue after the collapse of a shopping centre in Riga 21.11.2013, caused the death of 54 people. The reliability of a building is the practice of designing, constructing, operating, maintaining and removing buildings in ways that ensure maintained health, ward suffered injuries or death due to use of the building. Evaluation and improvement of existing buildings is becoming more and more important. For a large part of existing buildings, the design life has been reached or will be reached in the near future. The structures of these buildings need to be reassessed in order to find out whether the safety requirements are met. The safety requirements provided by the Eurocodes are a starting point for the assessment of safety. However, it would be uneconomical to require all existing buildings and structures to comply fully with these new codes and corresponding safety levels, therefore the assessment of existing buildings differs with each design situation. This case study describes the simple and practical procedure of determination of minimal reliability index β of existing steel structures designed by different codes than Eurocodes and allows to reassess the actual safety level of different structural elements of existing buildings under design load.